2014
DOI: 10.1002/anie.201410569
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical Hydrogen Production in Alkaline Solutions Using Cu2O Coated with Earth‐Abundant Hydrogen Evolution Catalysts

Abstract: Additional experimental details:All manipulations were carried out under atmospheric conditions, unless otherwise mentioned. All reagents were purchased from commercial sources and used without further purification. Millipore deionized water 18.2 M was used to prepare all the solutions. All electrochemical measurements were done using an Autolab potentiostat/galvanostat.A three-electrode configuration under front-side simulated AM 1.5 G solar illumination was used for photoelectrochemical hydrogen evolution m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
112
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 214 publications
(114 citation statements)
references
References 29 publications
1
112
1
Order By: Relevance
“…[28] Furthermore, catalysts for water oxidation are generally more efficient in alkaline solutions, for which there are several desirable Earth-abundant candidates. [21] At present, we found this TiO 2 overlayer approach to be insufficiently stable in alkaline conditions to allow a demonstration extended operation, but further study in this direction is ongoing, [29] since a stable and efficient photocathode in alkaline solution would be highly desirable.…”
Section: Tandem Device For Complete Water Splittingmentioning
confidence: 99%
“…[28] Furthermore, catalysts for water oxidation are generally more efficient in alkaline solutions, for which there are several desirable Earth-abundant candidates. [21] At present, we found this TiO 2 overlayer approach to be insufficiently stable in alkaline conditions to allow a demonstration extended operation, but further study in this direction is ongoing, [29] since a stable and efficient photocathode in alkaline solution would be highly desirable.…”
Section: Tandem Device For Complete Water Splittingmentioning
confidence: 99%
“…Moreover, TiO 2 -protected Cu 2 O photocathode had similar stability in base. 31 To further probe the origin of deactivation, the a-Si/Mo 2 C photocathodes after 1, 2, and 5 h of operation were analyzed by XPS. Mo 2 C was still found on the photocathodes, but its amount decreased with time.…”
mentioning
confidence: 99%
“…Although the applications of some p-type oxide semiconductors (e.g., CaFe 2 O 4 , p-LaFeO 3 /n-Fe 2 O 3 , Rhdoped SrTiO 3 ) in PEC devices have been reported, they are still faced with challenges such as a low hydrogen generation rate since the photocurrent densities at 0 V vs. RHE were usually less than 100 lA/cm 2 . 21-23 Paracchino et al 24 and Morales-Guio et al 25 reported highly active p-type Cu 2 O photocathode with proper catalysts for solar H 2 production. 6.3 mA/cm 2 of photocurrent at 0 V vs. RHE and 0.5 V vs. RHE of on-set potential were obtained under 100 mW/cm 2 simulated solar illumination in 1 M KOH.…”
mentioning
confidence: 99%